Rent Dissipation in Repeated Entry Games: Some New Results - Jean-Pierre Ponssard (Center for Economic Studies and ifo Institute (CESifo), 2004)
Two-player infinitely-repeated-entry games are revisited using a new Markov equilibrium concept. The idea is to have an incumbent facing a hit and run entrant. Rent dissipation no longer necessarily holds. It will not when competition is tough in case of entry. Similarities and differences with previous approaches are analyzed. Several economic illustrations are discussed.
Keywords: 330; rent dissipation; Markov equilibria; hit and run